Participatory Video: Subjects of Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
This video has English subtitles: click on the icon 'cc' to let them show. Participatory Video made by 12 young women farmers in Esteli, Nicaragua. They chose for the central theme of the PV to be: empowerment of rural women. The project is conducted by CCAFS with collaboration from the International Centre for Tropical Agriculture (CIAT), the local Fundacion Entre Mujeres (FEM) and with financial support from the CGIAR Research Program on Integrated Systems for the Humid Tropics (Humidtropics). Pictures can be found at: https://www.flickr.com/photos/cgiarclimate/sets/72157655398066271